La transformación del valor de las plantas tradicionales de los campesinos de los Andes (2017)
The research analyses the way in which the peasants of a community located in the Eastern Andean range, value their traditional plants, not only in the material order, but also with respect to their socio-cultural significance, particularly the symbolic, naturalistic and moral values. Thus, traditional plants illuminate the social, religious, environmental and economic context of the peasants, whose values are transformed according to the sphere of circulation (production, exchange and consumption) in which plants are found. The study was carried out using an ethnographic methodology, following a substantivist approach within the field of economic anthropology; hence, it was possible to recognise that value, as a model of action, guides the peasants behaviours and influences the way in which they withstand challenges brought by the new rurality. The study reveals that peasants are resilient, that they are heterogeneous in economic and social terms and that peasant economy provides a viable development model. Furthermore, the study highlights the feminization of ethnobotanical practices and knowledge and concludes that the study of value is central to solving some of the problems faced by Colombian peasants nowadays.--Tomado del Formato de Documento de Grado.